Electrocatalytic artificial carbonylation assay for observation of human serum albumin inter-individual properties - Vacek, Jan; Svrckova, Marika; Zatloukalova, Martina; Novak, David; Proskova, Jitka; Langova, Katerina; Galuszkova, Dana; Ulrichova, Jitka (Analytical biochemistry, 2018)
Human serum albumin (HSA) is a multifunctional protein with ligand binding, transporting and buffering properties. Posttranslational modifications and ligand binding processes are closely related to albumin final functional status. In the last few decades, HSA has been characterized using a broad spectrum of methods, but quantitative data on the HSA's modifications among individuals have not been reported. The investigations presented here are based on the non-denaturing electrocatalytic screening of HSA samples isolated from the blood serum of healthy subjects. The electrocatalytic responses of the native protein (Rnat) varied depending on its modifications among individuals, which enable us to express the inter-individual variability. Consequently, the native HSA samples were subjected to ex vivo carbonylation with 50 mM methylglyoxal for 36 h. The differences between Rnat and the responses of artificially carbonylated protein (Rmod) corresponded with inter-individual binding capacity variations (ΔR = Rnat-Rmod). The coefficients of variation for the Rnat and ΔR values of purified HSA samples were estimated to be 8.5 and 23.2%, respectively. A sensitive non-denaturing electrocatalytic assay was utilized to provide new data about albumin inter-individual variations and evaluate its oxidative modifications and binding capacity, which could be used for further studies targeting not only on HSA but also other clinically important proteins.
Keywords: karbonylace proteinů; Male; Adult; Protein Carbonylation; dospělí; mužské pohlaví; lidský sérový albumin; Electrochemical Techniques; Serum albumin; elektrochemické techniky; lidé; ženské pohlaví; Inter-individual variation; Humans; Electrocatalytic assay; Protein oxidation; Carbonylation; Serum Albumin, Human; Binding capacity; Female